2010
DOI: 10.1532/hsf98.20091131
|View full text |Cite
|
Sign up to set email alerts
|

Xiphoid Lower-Sternotomy Approach for Multivessel Revascularization of the Left Internal Mammary Artery to the Left Anterior Descending Artery and Right Internal Mammary Artery Inflow to the Other Vessels

Abstract: This minimally invasive technique is a useful alternative for complete revascularization. The sternal mammary supply and the upper part of the sternum are preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…We have done the MINI-OPCAB operation for single and multiple diseased vessels in more than 150 patients in different centers around the World; [5] of these cases, 70 patients underwent MINI-OPCAB operation with LIMA-LAD bypass from 1997 to 2021 in our Foundation, and 10 of them received concomitant hybrid revascularization. The mean age of the patients was 67 years, 23 (33%) had triple vessels disease, 18 (26%) had double vessels disease, 26 (37%) had single-vessel disease, and 3 (4%) had severe left main disease.…”
Section: Methodsmentioning
confidence: 99%
“…We have done the MINI-OPCAB operation for single and multiple diseased vessels in more than 150 patients in different centers around the World; [5] of these cases, 70 patients underwent MINI-OPCAB operation with LIMA-LAD bypass from 1997 to 2021 in our Foundation, and 10 of them received concomitant hybrid revascularization. The mean age of the patients was 67 years, 23 (33%) had triple vessels disease, 18 (26%) had double vessels disease, 26 (37%) had single-vessel disease, and 3 (4%) had severe left main disease.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, the work of Quan et al 1 remarks on the importance of the use of TTFM to reduce the incidence of preoperative myocardial injury during off‐pump coronary bypass surgery. Support of, in some ways, the recent expert opinion to promote the use of TTFM 10 …”
mentioning
confidence: 99%
“…3,4 Using TTFM, we can reconsider the most common use of OPCAB in situations of acute AMI where we can give the patient a better longterm survival, such as a Lima to Lad or arterial conduits in a young patient, or situations where we can do a MIDCAB and the variables, MINI OPCAB (lower middle incisions), or ROBOTIC operations. [5][6][7][8][9][10] A systematic review of the evidence and expert opinion statements, 11 concluded that although TTFM use may increase the cost and duration of the procedure and requires a learning curve, its cost/benefit ratio seems largely favorable, in view of the potential clinical consequences of graft dysfunction. These consensus statements will help to standardize the use of TTFM in clinical practice and provide guidance in clinical decision-making.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 We used the right mammary as inflow from many years in sternotomy off pump when the patient had a porcelain aorta, and we expanded this technique for the MINI OPCAB operation in multiple vessels. 25 With these and other, contributions regarding to different conduits adapted to the OPCAB, this surgery is today established worldwide. The future requires a bypass operation more minimally invasive, easy to reproduce and with possibilities to be done in the entire world.…”
mentioning
confidence: 99%